PEMANFAATAN DAUN WARU (Hibiscus tiliance L) SEBAGAI BAHAN BAKU DETERJEN - Luciana Supandi; Deny Ahmad Setiawan (Sainteks: Jurnal Sain dan Teknik, 2019)
SLS (Sodium Lauryl Sulfate) and LAS (Linear Alkyl Sulfonate) are active ingredients in detergents which have a negative impact on living things and the environment. To overcome these problems, one of the environmentally friendly alternative ingredients is waru leaves. The purpose of this study was to determine the benefits of waru leaves in their use for washing cloth, knowing the effectiveness of waru leaves as an active ingredient in cleaning stains and knowing the level of contamination of COD waste waru leaf extract. The composition of the detergent formula uses the experimental method with 1 factor, namely the concentration of waru leaves (80%, 82%, 84%, 86%, 88%). The sample selection stage is based on the parameters of pH, foam height, optimal viscosity. From this stage, two best formulas were obtained, namely 80% and 82% waru leaf extract. The two best samples were washed so that the best formula was 82%. Further testing is carried out to measure the level of waste contamination. The sample had a pH of 7.56, foam height of 4.10 cm, viscosity of 539.0, white degree of WI-CIE 155.02 and level of COD contamination of 308.25 mg / l. These results can prove that waru leaves can be used as detergent raw materials.